Malignant hyperthermia in young patient undergoing a surgical procedure under general anesthesia - Estéfano Arias Pastrana; Rosa Inés Carrascal Villero; Kevin Santiago Jiménez Escudero; Marlon Munera (Open Journal of Pain Medicine - Peertechz Publications, 2019)
Malignant hyperthermia (MH) is a hypermetabolic disease induced by the administration of anesthetic drugs in patients with genetic susceptibility. Its incidence ranges from 0.02% to 0.0153%. Here, we report the case of an 18-year-old male patient with no previous relevant surgical, medical, or family history of disease, who while undergoing a scheduled orthopedic surgical procedure under general anesthesia for the correction of left congenital talipes equinovarus, presented hyperthermia (41.8°C), muscular stiffness, tachycardia, trismus, increased blood pressure, and increased CO2 levels two hours after the induction of anesthesia. Malignant hyperthermia was suspected and managed following the protocol of the Colombian Anesthesiology and Resuscitation Association (SCARE), and MH diagnosis was confi rmed with response to dantrolene.